The double dimension of power and ideology in the theoretical perspective of the Critical Pedagogy (Praxis Educativa, 2012)
This article deals with the power and ideology question as well as their implications to develop a discourse which articulates, production of meanings with subjectivity, identity and difference, in relation to education. The subject matter is approached from the theoretical framework of critical pedagogy, specifically its two-dimensional conception of power, and the relations it keeps with the ideological processes of construction of subjectivity and the possibilities of resistance and counter-hegemony in education.
Keywords: power; bio-power; two dimensionality of power; ideology; body/subjec